Evaluating the Preparedness of a Process Industry to Deal with an Imminent Fire - Esmail AHMADIAN; Hamidreza MEHRI; Faeze SEPAHI-ZOERAM; Hamed MOHAMMADI (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Due to occurrence of fires in process industries, it is vital to implement crisis management systems in these industries and keep the readiness of these systems high. The purpose of this study is to evaluate the readiness of emergency response teams to deal with a possible fire in a process industry. Methods: This descriptive-analytical study was performed in 2019 in a gas refinery with a statistical population of 200 people. A questionnaire with Likert scale was designed through library and field studies for all teams participating in the firefighting process. Content Validity Ratio (CVR) and Content Validity Index (CVI) were used to measure validity and Cronbach's alpha coefficient was used to measure the reliability of the questionnaires. The collected data were entered into SPSS software version 24 and statistical analysis was performed at 95% significance level using One Way ANOWA test. Results: The results showed that the readiness of this refinery to deal with a possible fire was 68.3%, which among the 11 teams participating in this process, the security team with 53.48% had the lowest and the logistics team with 77.5% had the highest preparedness (P-value = 0.028). The highest CVR was for the safety team questionnaire (0.77) and the highest Cronbach's alpha coefficient was for the liaison team (0.92).  Conclusion: The results of this study showed that the readiness of this gas refinery in the firefighting process is satisfactory, although some teams, including the security team, are less prepared than other teams. Therefore, it is better to take intervention measures as soon as possible, including providing the necessary equipment and providing various trainings and maneuvers in order to increase the readiness of the teams.